2016
DOI: 10.1007/s11255-016-1432-7
|View full text |Cite
|
Sign up to set email alerts
|

Long-term efficacy of tonsillectomy as a treatment in patients with IgA nephropathy: a meta-analysis

Abstract: Long-term efficacy of tonsillectomy indicates that this treatment is helpful in inducing clinical remission and inhibiting development of end-stage renal disease in patients with IgAN and should be considered for addition into standard clinical treatment.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
28
0
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 31 publications
(31 citation statements)
references
References 35 publications
2
28
0
1
Order By: Relevance
“…We estimated that enrolling 107 patients would provide 80% power to detect a difference in tonsillectomy category with a 2-sided significance level of .05 in the analysis of the primary outcome, assuming an expected result of a 0.33 HR. 30 For all models, we graphically verified the proportionality of hazards for the Cox proportional hazards assumption using log plots. For missing values, we used the multivariate imputation method (eTable 3 in the Supplement ).…”
Section: Methodsmentioning
confidence: 99%
“…We estimated that enrolling 107 patients would provide 80% power to detect a difference in tonsillectomy category with a 2-sided significance level of .05 in the analysis of the primary outcome, assuming an expected result of a 0.33 HR. 30 For all models, we graphically verified the proportionality of hazards for the Cox proportional hazards assumption using log plots. For missing values, we used the multivariate imputation method (eTable 3 in the Supplement ).…”
Section: Methodsmentioning
confidence: 99%
“…The efficacy of tonsillectomy for IgAN has been clinically shown by a recent randomized controlled trials, 52 and it has also been published as a recommended treatment in IgAN clinical practice guidelines. 4 Recently, scientific evidence supporting the use of tonsillectomy has gradually accumulated, and this treatment is being developed not only in Asia 53,54 but also in Europe and the United States. 30,55 We hope that many additional researchers will publish new evidence linking the tonsils and kidneys in the future.…”
Section: Discussionmentioning
confidence: 99%
“…Nakata and his colleague found that serum GdIgA1 levels decreased more than half after tonsillectomy, which indicated that the palatine tonsils are probably major sites of GdIgA1-producing cells [18]. A meta-analysis suggested that TSP is helpful in inducing clinical remission and inhibiting the development of ESRD in IgA nephropathy patients [19].…”
Section: Discussionmentioning
confidence: 99%